Role of Siddha Varmam Therapy in Reducing Joint pain and Dependency on Medications in a RA patient - A single case study - Tiwari, Shweta; Sindhuja, Bhuvanagiri Sathya; Sankar, Injarapu; Reddy, Ram Mohan (Indian Journal of Integrative Medicine, 2024)
RA is an autoimmune disease characterized with symptoms related to inflammation in the joints resulting in pain, swelling, & deformity especially in the fingers, wrists, knees and ankles. In some cases, it may cause immobility in joint areas. Modern medicine suggests for expensive and long steroid dependency with less effect which has made many people to take up various alternative methods like Ayurveda, Homeopathy, Swedish massage which helps in reducing the symptoms in such cases. Alternative therapies like Siddha vaidyam; which is an ancient and old therapy has proved to be beneficial in managing the symptoms of RA. Yugi vaidhya Chindhamani mentioned Vazhi azhal keel Vayu and Uthiravatha suronitham as a vatha disease, the symptoms bear a core resemblance to RA. Varmam pressure therapy and massage (Thokanam) are introduced as a new modality within the existent Traditional and Complementary modalities to treat RA. It is one of the external therapies mentioned in Siddha literature helping in removal of toxins from body thus reducing pain and providing flexibility in joint areas. The purpose of this study was to assess the effects of various Varmam therapies on reducing joint pain and medication dependency based on American Rheumatism Association criteria: walking time, number of swollen and painful joints, joint count, grip strength, functions, ESR, and value of rheumatoid factor. A 45-year old female reported to the Chakrasiddh OPD with chief complaints of pain and swelling in both knee joints. She was given Siddha therapy for 1 month with 23 days in first phase and a week in second phase. Siddha therapy believes to instigate the Varma points where our energy is concentrated. The VAS used to determine the different variables showed a remarkable improvement in pain, stiffness and daily life activities. There was a reduced intake of steroids to once a week depending upon pain intensity. The ROM in the joint areas was seen more flexible and improved.